Cultura organizacional y desempeño docente en la Universidad Nacional del Centro del Perú - Llancari Morales, Rosario Ana (2020)
The research was intended to determine the relationship between organizational culture and teacher performance in the perception of teachers from the Universidad Nacional del Centro del Perú (UNCP); The descriptive level study and correlational descriptive design had a stratified probabilistic sample consisting of 88 teachers, to whom the Denison Organizational Culture Survey (Denison & Neale, 2000) was applied, whose reliability calculated using Cronbach's alpha was 0.949, and the Questionnaire of Teaching Performance adapted of Valdés (2006), whose reliability was 0.969. As a result, it was found that there is a relationship with a level of significance of 0.05, that there is a direct and significant relationship (Ʈ = 0.722) (Z = 1.96) between organizational culture and teaching performance; Likewise, 78.41% of teachers perceive a regular organizational culture; At the same time, 77.27% believe that teaching performance is good. It was concluded that there is a direct and significant relationship between organizational culture and teaching performance in the perception of teachers from the Universidad Nacional del Centro del Perú, therefore, to better organizational culture, better teaching performance, and vice versa.   DOI: https://doi.org/10.31876/sl.v4i1.45